OTORITAS GURU VERSUS PENCERAMAH MEDIA SOSIAL: ANALISIS PERGESERAN RUJUKAN KEAGAMAAN GENERASI MUDA - Sa'adah, Karomatus; Khairul Anam, Rifqi; Salsabila Makadina, Resfia; Sariroh, Toyiba (As-Sulthan Journal of Education, 2025)
This article examines the shifting religious reference among young people from classroom-based religious teachers to social media preachers who offer flexible, accessible, and emotionally engaging content. Using a library research method, the study analyzes literature on the authority of classroom teachers, the influence patterns of digital preachers, and the evolving religious preferences of students. The findings reveal that although religious teachers hold formal legitimacy within educational institutions, their impact is often limited by theoretical teaching approaches, minimal personal interaction, and a lack of connection to students’ everyday realities. In contrast, social media preachers establish authority through emotional closeness, relatable language, brief messages, and content that aligns with adolescents’ lived experiences. This shift provides positive outcomes by broadening access to religious knowledge and offering emotional support, yet it also poses risks such as shallow understanding, misinformation, and the weakening of teachers’ guiding roles. The article proposes strategies for teachers to remain relevant, including digital integration, context-based pedagogy, strengthening students’ digital literacy, and fostering open dialogue. Overall, the study highlights the need for harmonizing classroom learning with digital platforms to ensure both spaces effectively contribute to shaping young people’s religious understanding.